Elizabeth Bishop's queer lists. Issue 2 (4th May 2021) - Knorr, Alyse
ABSTRACT: Mid-20th-century American writer Elizabeth Bishop used lists in her notes to collect and select language for her poems and to think associatively on the page, blurring the worlds of the everyday and the literary. Bishop's archival drafts, published poetry, and published prose evince a poetics of list-making that provided the writer with a means of achieving highly accurate descriptions that convey a spontaneous mind in motion, turn the catalog into a surrealist camera, and queer class boundaries via a fragmentary, nonhierarchical grammar. Ultimately, this project offers a new approach to queering the archive by suggesting a politics of preservation that foregrounds the ephemeral.